Biodegradable peptide polymers as alternatives to antibiotics used in aquaculture. (22nd June 2022) - Ma, Pengcheng; Wu, Yueming; Jiang, Weinan; Shao, Ning; Zhou, Min; Chen, Yuan; Xie, Jiayang; Qiao, Zhongqian; Liu, Runhui
Abstract : Biodegradable peptide polymers display potent and broad-spectrum antibacterial activity in vitro, as well as strong therapeutic potential in vivo, as a promising alternative to antibiotics in aquaculture. Abstract : The pressure of antimicrobial resistance has forced many countries to reduce or even prohibit the use of antibiotics in feed. Therefore, it is an urgent need to develop alternatives to antibiotics to control infectious diseases in feed and aquaculture. To address this long-lasting challenge, we prepared peptide polymers that display potent and broad-spectrum activity against common pathogenic bacteria in aquaculture, low hemolysis and low cytotoxicity, and do not induce bacteria to develop resistance or cross-resistance to antibiotics. The optimal peptide polymer demonstrates strong in vivo therapeutic potential in an adult zebrafish infection model. Moreover, the optimal peptide polymer is biodegradable by enzymes into single amino acids and dipeptides to totally lose its antibacterial activity and, therefore, will not cause antimicrobial selective pressure. Our study suggests that peptide polymers are promising alternatives to antibiotics in aquaculture and open new avenues to address the global challenge of antimicrobial resistance.